HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN KUNJUNGAN ANTENATAL CARE (ANC) DI WILAYAH KERJA PUSKESMAS PEKAN HERAN - Riski Novera Yenita; Yuli Mushallimah (Pelantar Press, 2026)
This study aimed to investigate the relationship between the knowledge and attitude of pregnant women wah the frequency of Antenatal Care (ANC) visits m the Pekan Heran Community Health Center area. Purposive sampling method was employed to select 86 respondents as the research sample. Data were collected through a closed-ended questionnaire using Likert scale and true false response options. Data were analyzed using the chi-square test. The results of the stunty revealed a siguficant relationship between the level of knowledge of pregnant women and the frequency of ANC visits, with a p-value of 0.018 Additionally, a significant relationship was also found between the attitude of pregnant women and the frequency of ANC visits, with a p-value of 0.038. The analysis results indicated that the level of knowledge and attitude of pregnant women have a positive correlation with the number of ANC visits. This study holds important implications for efforts to enhance the participation of pregnant women in the ANC program, focusing on improving knowledge and cultivating a positive attitude